KETERAMPILAN 4C ABAD 21 DALAM PEMBELAJARAN PENDIDIKAN DASAR - Resti Septikasari; Rendy Nugraha Frasandy (Universitas Islam Negeri Imam Bonjol Padang, 2018)
Nations that are not ready to face the development of science and technology is growing very fast is certainly going to be left far behind with other nations. For that, in the 21st century, the school is required to have creative thinking, critical thinking and problem solving, communication, collaboration (collaboration) or so called 4C. The purpose of this study is to provide motivation for formal and informal education institutions to pay attention to the skills possessed by their students and provide a positive briefing to the child for the future. The type of research used is literature research (library research) with descriptive analytical method, which is a series of activities related to the method of collecting data library to describe the situation as it is. Data analysis used is content analysis.The results of this study are 1) the implementation of 21st century skills called 4C is the teacher must communicate well to students continuously in various circumstances. Socializing in students is necessary because the childhood is a period of play. When students play with peers, students will naturally engage in social interactions with their friends. Frequently invite students to communicate a positive impact to develop children's communication skills. This will stimulate the child's brain to imitate the use of good sentences. In addition 21st century skills students are trained to explain and exchange information with their friends when the learning process takes place, learn how to convey information properly, so that can be understood and understood by his friend. The teacher's role here is as a facilitator. 21st century skills can foster and enhance cooperation within a group to solve specific problems, increase their sense of tolerance for peer opinions, strive to think critically and creatively to solve problems of relating something.